Inequality of Opportunity Among Egyptian Children - Ersado, Lire (World Bank Group, Washington, DC, 2014)
This paper analyzes the level and trends in inequality of opportunity among Egyptian children during the 2000s. The analysis uses severall tools, including comparison of the distributions of early risks and outcomes across circumstance groups; estimation of the human opportunity index; measurement of the relative contributions of circumstances to inequality of opportunity; and decomposition of changes in inequality of opportunity and factors driving them over time. Egypt has made significant progress in the availability of and access to basic services for children and mothers, in some cases with an overall pro-poor effect. In particular, appreciable improvements have been made in healthcare utilization before and during pregnancy and immunizations. As a result, there has been a decline in inequality of opportunity over the past decade, largely attributable to increased coverage by basic services rather than through redistributive effects. However, there are areas of persistent and emerging concerns, including postnatal care utilization, nutrition, and schooling. Nutrition indicators have deteriorated during the 2000s, affecting a quarter of children regardless of their circumstances. Wide disparities in school enrollment persist, notably at the higher levels. Large regional disparities in access to basic infrastructure exist, with Upper Egypt and the Frontier Governorates lagging the rest of the country. Family background, especially parents' education and wealth, and geographic factors are key factors affecting child development outcomes in Egypt. While interventions targeted at the less advantaged circumstance groups may offer significant potential for enhancing overall equity in postnatal care utilization and schooling, a more inclusive approach would be needed to improve child nutrition outcomes.